Improving Mathematics Learning Outcomes in the Covid-19 Pandemic Era Through Contextual Teaching and Learning (CTL) Learning Models Using WhatsApp Groups for Class II Students of Kempong State Elementary School, Kapanewon Kalibawang, Kulon Progo Regency - Zumariyah Zumariyah (International Journal of Chemistry Education Research, 2022)
The purpose of this study was to determine the application of the Contexstual Teaching and Learning (CTL) learning method through WhatsApp Group. This type of research is classroom action research which is carried out in 2 cycles. Each cycle consists of 4 stages, namely planning, implementing actions, observing, and analyzing and reflecting. This research was conducted at Kempong State Elementary School, Kapanewon Kalibawang, Kulon Progo Regency. The results of this study indicate that the achievement of students in the first cycle at the first meeting the average value is 71.33 with learning completeness of 55.56% with the "Very Low" category, while the first cycle of the second meeting the average value is 75.67, the percentage is 66, 67% in the "Low" category, then in the second cycle of meeting 1 the average value was 82.33, the percentage of completeness was 77.78% with the "Enough" category. While at the second meeting of cycle II the average value was 87.44 in the "High" category with a completeness percentage of 100% with the "Very High" category. Meanwhile, teacher activities using the Contextual Teaching and Learning (CTL) learning model using WhatsApp Group in the first cycle of meeting 1 obtained an average score of 3.59, the presentation of the total score was 89.68%, with the category "Very Satisfactory". Meanwhile, in the second cycle of meeting 2, the average score was 3.84 with a presentation of 95.91%, in the "Very Satisfactory" category.